(untitled) (Medico Legal Update, 2020)
The process of key generation is utilized in different applications based on encryption techniques. The characteristics of the generated key should satisfy the required security as potential. The traditional techniques used for generating keys are based on various equations based on chaos maps or modulation for making these keys as one-time pads. Also, there are many techniques that utilized the block cipher or hash function for generating keys. In this paper, a retina image and bat-inspired algorithm are used for generating secure keys. Several processes have been applied to the input retina images like enhancement and edge detection processes. In the proposed technique, some parameters are adjusted for controlling the results and every output represents a bat solution and depending on the fitness function, the keys are generated. These generated keys are tested and evaluated using NIST tests. As a case study, some images are encrypted using the generated keys and the obtained encrypted images passed all the required security tests.